2022
DOI: 10.1159/000525616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sites of Metastatic Dissemination on Survival in Advanced Gastroesophageal Adenocarcinoma

Abstract: Background: Metastatic gastroesophageal adenocarcinoma (GEA) is a heterogeneous disease with an overall poor prognosis. The impact of sites of metastatic dissemination on survival is not well characterized. This study aims to evaluate whether certain sites of metastatic disease impacts survival. Methods: A retrospective analysis of 375 patients with metastatic GEA treated at the Princess Margaret Cancer Centre from 2006 to 2016 was performed. Overall survival (OS) and progression-free survival (PFS) were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Other studies suggested that the presence of lung or bone metastases is an independent risk factor for decreased survival. 28 Additionally, while in the UVA, there was a significant association between worse OS and SB, the MVA showed that only patients with a high SB cohort had a significantly increased risk of death.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies suggested that the presence of lung or bone metastases is an independent risk factor for decreased survival. 28 Additionally, while in the UVA, there was a significant association between worse OS and SB, the MVA showed that only patients with a high SB cohort had a significantly increased risk of death.…”
Section: Discussionmentioning
confidence: 90%